What is required to facilitate implementation of Swedish physical activity on prescription? - interview study with primary healthcare staff and management - Catharina Gustavsson; Maria Nordqvist; Kristina Bröms; Lars Jerdén; Lena V. Kallings; Lars Wallin (BMC, 2018)
Abstract Background The method, Swedish Physical Activity on Prescription (SPAP), has been launched in Swedish healthcare to promote physical activity for prevention and treatment of lifestyle related health disorders. Despite scientific support for the method, and education campaigns, it is used to a limited extent by health professionals. The aim of the study was to describe the views of health professionals on perceived facilitators, barriers and requirements for successful implementation of SPAP in primary healthcare. Methods Eighteen semi-structured interviews with stakeholders in SPAP, i.e. ten people working in local or central management and eight primary healthcare professionals in two regional healthcare organisations, were analysed using qualitative content analysis. Results We identified an overarching theme regarding requirements for successful implementation of SPAP: Need for knowledge and organisational support, comprising four main categories: Need for increased knowledge and affirmative attitude among health professionals; Need for clear and supportive management; Need for central supporting structures; Need for local supporting structures. Knowledge of the SPAP method content and core components was limited. Confidence in the method varied among health professionals. There was a discrepancy between the central organisation policy documents declaring that disease preventive methods were prioritised and a mandatory assignment, while the health professionals asked for increased interest, support and resources from management, primarily time and supporting structures. There were somewhat conflicting views between primary healthcare professionals and managers concerning perceived barriers and requirements. In contrast to some of the management's beliefs, all primary healthcare professionals undisputedly acknowledged the importance of promoting physical activity, but they lacked time, written routines and in some cases competence for SPAP counselling. Conclusion The study provides knowledge regarding requirements to facilitate the implementation of SPAP in healthcare. There was limited knowledge among health professionals regarding core components of SPAP and how to practise the method, which speaks for in-depth training in the SPAP method. The findings highlight the importance of forming policies and guidelines and establishing organisational supporting structures, and ensuring that these are well known and approved in all parts of the healthcare organisation.